The effect of geometer sketchpad on secondary school students’ mathematical intelligence - Ma, Yu Fei (Frontiers in Education, 2025)
In recent years, the impact of teaching technology on students’ mathematical intelligence has received essential academic attention. Students’ mathematical intelligence is a crucial criterion to measure their mathematical understanding and problem-solving ability. Geometry Sketchpad (GSP) is a dynamic geometry software which effectively promotes mathematical cognitive development through its interactive visualization features. Given that the exact function of GSP remains inadequately investigated. This study aims to analyze the impact of GSP on mathematical intelligence in two key dimensions: geometric imagination and functional cognition. By following the PRISMA guidelines, 26 articles from Google Scholar, Web of Science and Scopus were screened for data analysis. A major finding is that GSP has an impact on the development of students’ mathematical intelligence. For example, the dynamic visualization feature of GSP can enhance students’ geometric imagination skills and spatial reasoning. Also, using GSP is conducive to improving students’ problem-solving skills and deepening their understanding of geometric concepts. In addition to demonstrating the functions of GSP, I constructed four types of conic curves. By reading this article, readers can easily understand the applications of GSP. Mathematics teachers can understand the functions of GSP and use it in teaching process. Peer researchers can comprehend limitations of the literature in this field.